2015
DOI: 10.1016/j.jcin.2015.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Escalating Loading Dose Regimens of Ticagrelor in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: ST-segment elevation myocardial infarction patients undergoing PPCI frequently exhibit impaired response to ticagrelor in the early hours after drug administration, which cannot be overcome by increasing LD regimens. These PD findings are largely attributed to an impaired PK profile, indicating a delay in drug absorption compared with that reported in stable clinical settings. (High Ticagrelor Loading Dose in STEMI; NCT01898442).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 25 publications
5
52
1
2
Order By: Relevance
“…Similar conclusions were drawn from a post hoc subanalysis of the HARMONIC study, where STEMI patients had decreased overall and delayed maximum ticagrelor and AR-C124910XX concentrations when compared with NSTEMI patients, which subsequently led to weaker platelet inhibition in STEMI [12]. Likewise, Franchi et al reported that STEMI patients suffer from impaired ticagrelor absorption in comparison with healthy subjects and patients with stable coronary artery disease, which was reflected by delayed onset of platelet inhibition and importantly was also observed in opioid-naive STEMI patients [9]. In contrast, NSTEMI patients not receiving morphine have ticagrelor PK/PD profile similar to that of patients with stable coronary artery disease [22].…”
Section: Discussionsupporting
confidence: 74%
“…Similar conclusions were drawn from a post hoc subanalysis of the HARMONIC study, where STEMI patients had decreased overall and delayed maximum ticagrelor and AR-C124910XX concentrations when compared with NSTEMI patients, which subsequently led to weaker platelet inhibition in STEMI [12]. Likewise, Franchi et al reported that STEMI patients suffer from impaired ticagrelor absorption in comparison with healthy subjects and patients with stable coronary artery disease, which was reflected by delayed onset of platelet inhibition and importantly was also observed in opioid-naive STEMI patients [9]. In contrast, NSTEMI patients not receiving morphine have ticagrelor PK/PD profile similar to that of patients with stable coronary artery disease [22].…”
Section: Discussionsupporting
confidence: 74%
“…Commonly performed cotreatment with morphine may further negatively influence the rate of absorption of P2Y 12 inhibitors, including ticagrelor among patients with STEMI 13. Attempts to improve platelet inhibition using higher loading doses in a setting of primary PCI have failed to show effect 15 16. However, administration of crushed ticagrelor tablets reduced platelet reactivity up to 50% at 1 h compared with integral tablets 17 18.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, Franchi et al evaluated different loading doses of ticagrelor and the effect of morphine in 52 STEMI patients. 23 Absorption of ticagrelor was slightly delayed by morphine (mean time to maximal concentration in plasma 5.6 versus 4.9 hours), and platelet reactivity levels were higher at 30 minutes after loading dose (P=0.018), but not significantly different at all other study time points between patients who took morphine and those who did not. Differences in rates of high residual platelet reactivity were not significant, and morphine was not an independent predictor of high on-treatment platelet reactivity.…”
Section: Prasugrel and Ticagrelormentioning
confidence: 84%